Insulin resistance induced by maximal exercise correlates with a post-exercise increase in uridine concentration in the blood of healthy young men - Dudzinska, W; Lubkowska, A; Jakubowska, K; Suska, M; Skotnicka, E (Physiological research, 2013)
Uridine is postulated to participate in the development of insulin resistance. Since exercise is an effective tool in the treatment of insulin resistance it appeared justified to assess the impact of maximal exercise on plasma uridine and insulin sensitivity indices (e.g. insulin and HOMA-IR) in healthy subjects. The study included forty-four healthy males (18.5+/-2.92 years, VO₂max 50.2+/-6.26 ml kg⁻¹ min⁻¹). Subjects performed a single maximal exercise on a bicycle ergometer. Blood samples were taken three times: immediately before exercise, immediately after exercise and at the 30(th) min of rest. Uridine concentrations were determined in the whole blood using high-performance liquid chromatography. Serum insulin levels were measured by a specific ELISA method. Insulin sensitivity was assessed by homeostasis model assessment method (HOMA-IR). A maximal exercise-induced increase in the concentration of uridine correlated with post-exercise increases in insulin levels and HOMA-IR. Our results indicate a relationship between the concentration of uridine in the blood and indicators of insulin sensitivity in healthy subjects. We are the first to demonstrate that a maximal exercise-induced increase in the concentration of uridine is correlated with post-exercise increases in insulin levels and HOMA-IR in healthy subjects. It appears that uridine may be an indicator of insulin resistance.
Keywords: homeostáza; Enzyme-Linked Immunosorbent Assay; Anaerobic Threshold; Anthropometry; mladý dospělý; Adolescent; vysokoúčinná kapalinová chromatografie; lidé; Blood Glucose; cvičení; Homeostasis; Insulin; antropometrie; Uridine; anaerobní práh; Humans; Chromatography, High Pressure Liquid; ELISA; Male; Exercise Test; Insulin Resistance; Young Adult; inzulinová rezistence; uridin; mužské pohlaví; Exercise; inzulin; krevní glukóza; mladiství; zátěžový test